1998
DOI: 10.1095/biolreprod59.2.330
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Insulin-Like Growth Factor I in Bovine Seminal Plasma and Its Receptor on Spermatozoa: Influence on Sperm Motility1

Abstract: Insulin-like growth factor I (IGF-I) has been identified in human seminal plasma. This study was conducted to determine whether IGF-I is present in bovine seminal plasma, whether sperm cells express the IGF-I receptor (IGF-IR), and whether IGF-I affects sperm motility. Semen samples were collected from bulls by electroejaculation and maintained at 37 degrees C, and motility of sperm was assessed. After centrifugation to separate sperm cells from seminal plasma, the seminal plasma was submitted to a validated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
101
2
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 42 publications
9
101
2
6
Order By: Relevance
“…Similar results were found in previous research using bovine (Henricks et al, 1998), human (Miao et al, 1998), equine (Chanpion et al, 2002) and swine (Miah et al, 2008) samples. IGF-I might act as a chemokinetic factor involved in the regulation of cell movement, because IGF-I receptors have been reported to be found on spermatozoa (Henricks et al, 1998). Spermatozoal motility and velocity indirectly reflect their mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were found in previous research using bovine (Henricks et al, 1998), human (Miao et al, 1998), equine (Chanpion et al, 2002) and swine (Miah et al, 2008) samples. IGF-I might act as a chemokinetic factor involved in the regulation of cell movement, because IGF-I receptors have been reported to be found on spermatozoa (Henricks et al, 1998). Spermatozoal motility and velocity indirectly reflect their mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
“…IGF-I has been suggested to be an important factor for germ cell development, maturation and motility of the spermatozoa (Henricks et al, 1998;Glander et al, 1996;Vickers et al, 1999). Furthermore, IGF-I is believed to be involved in spermatogenesis (Tsutura and O'Brien, 1995) and steroidogenesis (Saez, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical substances have been linked to metabolic control of the sperm cell, including the growth factor insulin-like type I (IGF-I) in bovine (Henricks et al, 1998) and swine (Silva et al, 2011). According to previous studies in buffalo, this substance acts as a metabolic activator of sperm that is involved in cell movement (motility and intensity of movement) by increasing carbohydrate metabolism, and consequently, the fertilising capacity of the sperm (Selvaraju et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, total IGF-I was measured. For instance, in buffaloes, Selvaraju et al (2009) (Henricks et al, 1998) in bovine seminal plasma, and in stallion from 10.2 to 10.4 ng/mL (Macpherson et al, 2002). These values show that the levels in boars and stallions are similar to those in humans (Lackey et al, 2002), but much lower than those found in cattle and buffaloes.…”
Section: Discussionmentioning
confidence: 89%
“…Receptors for IGF-I have also been identified in these cells (Wang and Hardy, 2004;Vanelli et al, 1998). Additionally, these receptors have been identified in other cells such as secondary spermatocytes, spermatids (Vanelli et al, 1998) and spermatozoa (Henricks et al, 1998).…”
Section: Introductionmentioning
confidence: 96%